Plan de negocio para la construcción y reparación de canchas de tenis sintéticas a base de caucho importado de los Estados Unidos - Alarcón Fuentes, Diego Andrés (2018)
In the country there is a positive environment for projects related to sport, since sports activity will improve the quality of life of the population. In search of taking advantage of this positive situation, this research is developed with the objective of "Developing a business plan for the creation of a synthetic folder importing company for tennis courts from the United States of America, to commercialize it at a national level, and determine its feasibility ". In its development it includes the analysis of environments from which it appears that the project has a high sensitivity to external factors, and that the industry and the environment are attractive, favorable and present opportunities that could be exploited, since tennis is one of the five most practiced sports in the country. The client's study shows that there is a high demand that justifies the project, because the hard courts are the most popular in modern tennis, and that a value offer must be generated aimed at continuous improvement, which gives priority to the quality of the product and service, adequate attention, and promotion mainly through digital channels and social networks, to have a greater chance of success. Through the study of operations, the organizational model is established, which will allow the development of an efficient management model to develop efficient internal processes, be socially and environmentally responsible, generate an adequate return, and contribute to improving the quality of life of its human resources. When evaluating the flows that would be generated when operating the project, from the perspective of the project and the investor, it is determined that it is feasible, feasible and profitable since the financial feasibility indicators VAN, TIR and PRI are favorable, but that the variations that could have critical values.